2022
DOI: 10.1002/lary.30061
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Laryngopharyngeal Reflux and Obstructive Sleep Apnea: A Population‐Based Study

Abstract: Objectives/Hypothesis: To evaluate the presence of laryngopharyngeal reflux (LPR) and the potential association between presence of LPR symptoms and obstructive sleep apnea (OSA) in a representative sample from a population-based study.Study Design: Cross-sectional study.Methods: Participants of the follow-up of the Epidemiological Sleep Study were evaluated. Sleep was assessed through questionnaires and polysomnography. The presence of LPR was based on the questionnaire Reflux Score Index (RSI), and scores hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Obesity was found to be the strongest association with reflux [ 84 ]. Similarly, in a study by Campanholo et al [ 85 ], acid reflux was reported in 45% of the cases with OSA. The severity of OSA was not associated with the Reflux Symptom Index (RSI) score.…”
Section: Acid Reflux – Chronic Cough – Dysphagiamentioning
confidence: 55%
See 1 more Smart Citation
“…Obesity was found to be the strongest association with reflux [ 84 ]. Similarly, in a study by Campanholo et al [ 85 ], acid reflux was reported in 45% of the cases with OSA. The severity of OSA was not associated with the Reflux Symptom Index (RSI) score.…”
Section: Acid Reflux – Chronic Cough – Dysphagiamentioning
confidence: 55%
“…The severity of OSA was not associated with the Reflux Symptom Index (RSI) score. Age, smoking, but not BMI, were associated with acid reflux [ 85 ]. Radovanovic et al [ 86 ▪ ] found that the prevalence of acid reflux symptoms was not different in patients with OSA compared with snorers and nonsnorers, after purposely excluding key confounding factors, such as obesity and alcohol abuse.…”
Section: Acid Reflux – Chronic Cough – Dysphagiamentioning
confidence: 99%
“…We identified 26 studies 8 , 9 , 20–43 involving LPR incidence in OSAHS patients, as shown in Table 1 . Ten articles 9 , 22 , 24 , 26 , 29 , 33 , 36 , 39 , 42 , 43 compared the clinical characteristics of patients with LPR-positive OSAHS and LPR-negative OSAHS ( Table 2 ). Six studies 10 , 25 , 27–29 , 36 provided Spearman’s or Pearson’s CORs between RSI score and AHI score.…”
Section: Resultsmentioning
confidence: 99%
“…Weiter erwies sich in dieser Untersuchung, dass Adipositas die stärkste Assoziation mit Reflux ist [26]. Eine weitere Studie berichtet in 45% der Fälle mit OSAS über sauren Reflux [27].…”
Section: Laryngopharyngealer Refluxunclassified